The Unsaturated Hydromechanical Coupling Model of Rock Slope Considering Rainfall Infiltration Using DDA. (19th December 2017) - Liu, Xianshan; Xu, Ming
Abstract : Water flow and hydromechanical coupling process in fractured rocks is more different from that in general porous media because of heterogeneous spatial fractures and possible fracture-dominated flow; a saturated-unsaturated hydromechanical coupling model using a discontinuous deformation analysis (DDA) similar to FEM and DEM was employed to analyze water movement in saturated-unsaturated deformed rocks, in which the Van-Genuchten model differently treated the rock and fractures permeable properties to describe the constitutive relationships. The calibrating results for the dam foundation indicated the validation and feasibility of the proposed model and are also in good agreement with the calculations based on DEM still demonstrating its superiority. And then, the rainfall infiltration in a reservoir rock slope was detailedly investigated to describe the water pressure on the fault surface and inside the rocks, displacement, and stress distribution under hydromechanical coupling conditions and uncoupling conditions. It was observed that greater rainfall intensity and longer rainfall time resulted in lower stability of the rock slope, and larger difference was very obvious between the hydromechanical coupling condition and uncoupling condition, demonstrating that rainfall intensity, rainfall time, and hydromechanical coupling effect had great influence on the saturated-unsaturated water flow behavior and mechanical response of the fractured rock slopes.